Comparative Empirical Analysis of Macroeconomic Variables, Firm Characteristics and Stock Return in Four South East Asian Countries - Tan, Ee Chain (2013)
This paper investigates the role of macroeconomic factors and firm characteristics in explaining stock return in four countries, namely, Malaysia, Singapore, Thailand and Indonesia. The factors model is employed for two time intervals, namely, sub-period A (from July 2003 to June 2007) and subperiod B (from July 2007 to June 2011) to examine the change in relationship between macroeconomic variables and stock return as well as firm characteristics and stock return during these two periods. This study uses the following macroeconomic variables: growth in industrial production, change in consumer price index, growth of money supply, change in exchange rate, change in term structure and growth rate of international crude oil price. The analysis is based on stock portfolios rather than stock indices to refine the portfolio based on the firm characteristics. In portfolio construction, three firm characteristics are used: market equity, book-to-market ratio and price to equity ratio. Descriptive statistical result shows high book-to market portfolio consistently outperform low and medium book-to-market portfolio in term of monthly average stock return for both sub-periods. The multi-regression model is formed by using portfolios as dependent variables and macroeconomic variables as independent variables. The Ordinary Least Square method is deployed to evaluate the relationship between portfolio stock return and macroeconomic variables. Empirical findings reveal that the relationship between macroeconomic variables and stock return changes with different time period (sub-period A or sub-period B), different countries and different portfolios. The different portfolios enable us to present a crosssectional view of the overall stock market in Malaysia, Singapore, Thailand and Indonesia.